Agro -Allied Small And Medium Scale Business And Economic Growth Of Nigeria (1976-2021) - Babatunde, Bayode Olusanya; Olagunju, Adebayo; Onikoyi, Idris Adegboyega; Oginni, B.O; Kazeem, B.L.O. (Acta Universitatis Danubius. Œconomica, 2022)
Agro-allied industries rely on agriculture for raw materials in order to produce finished goods that are helpful to livestock and people. The study examined the impact of agro allied small and medium scale business on economic growth of Nigeria between 1976 and 2020. The data was sourced from CBN Statistical Bulletin and analysed using econometric techniques such as ordinary least square, error correction model etc with the aid of EViews software. The Regression result showed that a positive and significant relationship exist between agro allied SMEs has a significant impact on real gross domestic product (R2 =0.586, Adjusted R2 = 0.577, p value= 0.02). The study concluded that agro allied small and medium scale business has moderate positive impact on economic growth of Nigeria. This study therefore recommends that the emphasis should be on modern technology to improve agro allied business to make economy more functional, relevant and growth driven.